NKp44 and Natural Cytotoxicity Receptors as Damage-Associated Molecular Pattern Recognition Receptors - Horton, Nathan C.; Mathew, Porunelloor A. (Frontiers in Immunology, 2015)
Natural Killer (NK) cells are a key constituent of the innate immune system, protecting against bacteria, virally infected cells, and cancer. Recognition and protective function against such cells is dictated by activating and inhibitory receptors on the surface of the NK cell which bind to specific ligands on the surface of target cells. Among the activating receptors is a small class of specialized receptors termed the Natural Cytotoxicity Receptors (NCRs). Comprised of NKp30, NKp46, and NKp44, the NCRs are key receptors in the recognition and termination of virally infected and tumor cells. Since their discovery over ten years ago, ligands corresponding to the NCRs have largely remained elusive. Recent identification of the cellular ligands for NKp44 and NKp30 as exosomal proliferating cell nuclear antigen (PCNA) and HLA B associated transcript 3 (BAT3) respectively, implicate that NCRs may function as receptors for Damage Associated Molecular Pattern (DAMP) molecules. In this review, we focus on NKp44, which surprisingly recognizes two distinct ligands resulting in either activation or inhibition of NK cell effector responses in response to tumor cells. The inhibitory function of NKp44 requires further study as it may play a pivotal role in placentation in addition to being exploited by tumors as a mechanism to escape NK cell killing. Finally, we suggest the NCRs are a class of pattern recognition receptors which recognize signals of genomic instability and cellular stress via interaction with the c-terminus of DAMP molecules localized to the surface of target cells by various coligands.